ENSURING EQUITABLE AND QUALITY PRIMARY AND SECONDARY EDUCATION: AN ISLAMIC PERSPECTIVE TOWARD A FAITHFUL, INTELLIGENT, AND GLOBALLY COMPETITIVE GENERATION - Baidawi, Imam; Sa’diyah, Halimatus (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
This paper explores the intersection between Islamic educational philosophy and contemporary efforts to ensure equitable and quality primary and secondary education. Drawing on classical sources such as the Qur’an, Hadith, and seminal worksby scholars like Al-Ghazali and Ibn Khaldun, the study articulates an Islamic vision of education that balances faith, intellect, and moral character. Through qualitative library-based research and thematic analysis, the paper examines how Islamic valuessuch as justice (‘adl), knowledge (‘ilm), and holistic development (tarbiyah) can complement global educational goals, particularly those outlined in SDG 4. The findings reveal that the Islamic approach offers both normative insights and practical strategies for addressing systemic inequities, fostering inclusive learning environments, and developing ethically grounded learners who are also globally competent. Rather than positioning itself in opposition to modern educational standards, the Islamic perspective enriches them by embedding purpose, ethics, and community responsibility into the learning process. This study contributes toeducational theory by offering a culturally rooted yet universally relevant model that bridges spiritual development with academic and global excellence